2018
DOI: 10.1128/jvi.01599-17
|View full text |Cite
|
Sign up to set email alerts
|

The Absence of DHHC3 Affects Primary and Latent Herpes Simplex Virus 1 Infection

Abstract: UL20, an essential herpes simplex virus 1 (HSV-1) protein, is involved in cytoplasmic envelopment of virions and virus egress. We reported recently that UL20 can bind to a host protein encoded by the zinc finger DHHC-type containing 3 () gene (also known as Golgi-specific DHHC zinc finger protein [GODZ]). Here, we show for the first time that HSV-1 replication is compromised in murine embryonic fibroblasts (MEFs) isolated from GODZ mice. The absence of GODZ resulted in blocking palmitoylation of UL20 and alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 62 publications
2
20
0
1
Order By: Relevance
“…Absence of SPP in SPP-inducible knockout mice alters cellular transcript expression in cornea and TG of infected mice. We have previously shown that virus replication directly correlates with the presence of immune infiltrates in corneas of infected mice (40)(41)(42)(43). This result suggests that mice lacking SPP have less virus replication and fewer viral transcripts in their corneas and TG ( Fig.…”
Section: Resultsmentioning
confidence: 80%
“…Absence of SPP in SPP-inducible knockout mice alters cellular transcript expression in cornea and TG of infected mice. We have previously shown that virus replication directly correlates with the presence of immune infiltrates in corneas of infected mice (40)(41)(42)(43). This result suggests that mice lacking SPP have less virus replication and fewer viral transcripts in their corneas and TG ( Fig.…”
Section: Resultsmentioning
confidence: 80%
“…We recently reported exacerbated eye disease in BALB/c mice infected with HSV-CD80 compared to mice infected with the parental, LAT(Ϫ) virus (35). In contrast to BALB/c mice, C57BL/6 mice are refractory to eye disease following ocular infection with HSV-1 strain McKrae or McKrae-derived recombinant viruses (37,38). To determine whether HSV-CD80 infection exacerbates eye disease in C57BL/6 mice, mice were ocularly infected with 2 ϫ 10 5 PFU per eye of HSV-CD80 or WT McKrae.…”
Section: Resultsmentioning
confidence: 99%
“…Ocular infection. Mice were infected ocularly with 2 ϫ 10 5 PFU of HSV-1 strain McKrae per eye in 2 l of tissue culture medium as an eye drop without corneal scarification, as we described previously (37,38).…”
Section: Methodsmentioning
confidence: 99%
“…Unsurprisingly, bioinformatics analysis identified a long list of targeted genes ( Supplementary Table S3). A few of these genes have previously been reported to be associated with HSV productive infection (Supplementary Table S3, genes marked with asterisks), such as phosphatidylinositol binding clathrin assembly protein (PICALM) (Carter 2011), zinc finger DHHC-type containing 3 (ZDHHC3) (Wang et al 2018), aquaporin 4 (AQP4) (Martinez-Torres et al 2007), SUMO1/sentrin specific peptidase 7 (SENP7) (Cui et al 2017), and inhibitor of kappa light polypeptide gene enhancer in B-cells, kinase beta (IKBKB) (Gregory et al 2004). These candidate targets offer opportunities for further studies to understand the detailed mechanisms of the molecular mechanisms underlying HSV infection and establishment toward developing new treatment strategies.…”
Section: Discussionmentioning
confidence: 99%